2016
DOI: 10.1177/0363546516651440
|View full text |Cite
|
Sign up to set email alerts
|

The Orientation and Variation of the Acromioclavicular Ligament

Abstract: Anatomic reconstruction, based on the current findings in combination with findings regarding the coracoclavicular ligament, could facilitate improved outcome in the treatment of AC joint disruption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
48
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 20 publications
3
48
2
Order By: Relevance
“…To reconstruct such a ligamentous structure and optimize the biomechanical function, points of fixation should be placed within these anatomical areas. The data of our study suggest that the highest BMD of the acromion can be found just within the origin of the superior AC ligament as described by Nakazawa et al [13].…”
Section: Discussionsupporting
confidence: 83%
“…To reconstruct such a ligamentous structure and optimize the biomechanical function, points of fixation should be placed within these anatomical areas. The data of our study suggest that the highest BMD of the acromion can be found just within the origin of the superior AC ligament as described by Nakazawa et al [13].…”
Section: Discussionsupporting
confidence: 83%
“…9 This may not be easily pinpointed intraoperatively, as previous studies have shown the ACLC to have several variations of anatomy and injury pattern (clavicle-sided, oblique, midpoint, and acromion-sided ACLC tear) in an acute AC dislocation. 30,31 Moreover, in chronic and revision cases, the ACLC may be irreparable and reconstruction may be necessary. In contrast to the current technique described, the obvious downside of the dermal allograft include an inherent additional monetary cost, along with the potential for added stress to the distal clavicle to potentially fracture.…”
Section: Discussionmentioning
confidence: 99%
“…The AC ligament complex spans between the acromion and the distal clavicle and has been described by multiple authors as having anterior, posterior, superior, and inferior components; 4,5 however, numerous cadaveric studies have failed to identify the inferior ligament up to 50% of the time. [6][7][8] Nakazawa et al 9 divided the ligament into 2 parts: superoposterior (SP) and anteroinferior (AI). Despite consistent presence of the SP bundle, the AI bundle varied in thickness and location, spanning the inferior part of the joint in only 42% of the investigated shoulders.…”
Section: Anatomymentioning
confidence: 99%